Qur’anic Recitation as a Psychological Therapy: An Intervention Model for Mental Health - Mawaddah, Alfi Wirda; Shofiah, Vivik; Rajab, Khairunnas (unprimdn.ac.id, 2025)
Qur'anic recitation has excellent potential as a psychological therapy method to address mental health issues such as stress, anxiety, and depression. This study aims to analyze the effectiveness of recitation through a multidimensional approach in improving individual mental well-being. The method employed is a qualitative literature study involving the analysis of relevant national and international journals. The results showed that Qur'anic recitation contributes to lowering stress levels, improving mindset, and strengthening emotional resilience through spiritual closeness. However, challenges such as a lack of understanding of the verses' meaning and indiscipline in recitation practice are obstacles that need to be overcome. This study recommends a strategy of professional mentoring, the utilization of digital technology, and the strengthening of tilawah-based communities to optimize its effectiveness. The findings reinforce the potential of tilawah as a model of Islamic psychological therapy that can be integrated into modern mental health practices.